Differential Adoption of Climate Smart Agriculture: Interventions in Odisha - Das, Usha; Ansari, M A; Ghosh, Souvik (Journal of Agricultural Extension Management, 2024)
Climate Smart Agriculture (CSA) is a strategy for restructuring and reorienting agricultural production systems and food value chains to promote long-term development and food security in the face of climate change. It is a novel way to chart growth trajectories that can make agriculture more productive and sustainable, as well as more adapted to climate change mitigation and adaptation. Present study was undertaken in one of the most vulnerable State’s of India i.e., Odisha. The unique combination of coastal and non-coastal ecosystems in Odisha facilitated to document varied types of CSA interventions to face the wrath of climate change effects. The study was conducted in a climatically vulnerable coastal (Kendrapara) and non-coastal district (Dhenkanal) of Odisha with 200 farmers. These farmers were chosen purposively with the criteria underlying that those were the beneficiaries of NICRA (National Innovations for Climate Resilient Agriculture) project. The NICRA project is the flagship program launched by Indian Council of Agricultural Research (ICAR) to address all the climate related issues in India. Using a semi-structured questionnaire, the differential adoption of farmers for various types of CSA interventions is presented in this article. This article will guide the future researches in the similar fields and for policy advocacy to scale up the interventions that are location specific and witness better adoption by the farmers.